Tungsten and molybdenum co-precipitation by α-benzoinoxime for activation analysis of tungsten - Korob, Ricardo Osvaldo (1976)
Fil: Korob, Ricardo Osvaldo Comisión Nacional de Energía Atómica; Argentina